Long-Term Results of Limberg Flap Procedure for Treatment of Pilonidal Sinus: A Report of 200 Cases - Topgül, K; Özdemir, E; Kiliç, K; Gökbayir, H; Ferahköse, Z (Lippincott Williams & Wilkins, 2003)
PURPOSE: In the past, various methods of surgical or nonsurgical treatment of sacrococcygeal pilonidal sinus have been used. The most common problem in the treatment of this disease is recurrence. In the present study, our aim was to determine the long-term results of the Limberg flap procedure. METHODS: We present 200 consecutive patients with pilonidal sinus who underwent the Limberg flap procedure between 1992 and 2001. Twenty-six (13 percent) of the 200 patients were operated on because of recurrent pilonidal sinus. Under general or local anesthesia, all sinus tracts were resected en bloc, and the Limberg flap was prepared from the gluteal region. We used a suction drain. We met all patients and recorded their complaints and complications of treatment. RESULTS: Five sinuses recurred (2.5 percent). Minimal flap necrosis occurred in only six patients (3 percent). In three patients (1.5 percent), seroma developed. Wound infection occurred in three patients (1.5 percent). The mean hospital stay was 3.1 days, whereas the mean time to return to work was 12.8 days. CONCLUSION: The Limberg flap procedure is a good treatment choice for pilonidal sinus because of its low complication rate, the short time to return to normal activity, and good long-term results. This procedure has good postoperative results and is a comfortable surgical method for the patient.